More is less: mass-flowering fruit tree crops dilute parasite transmission between bees. Issue 9 (August 2021) - Piot, Niels; Eeraerts, Maxime; Pisman, Matti; Claus, Gregor; Meeus, Ivan; Smagghe, Guy
Graphical abstract: Highlights: Pollen of the brood cells of Osmia spp. contain parasites. Disturbance of the plant-pollinator network results in changes in parasite prevalence on flowers. Parasite transmission is lower during the bloom of mass-flowering fruit crops than after bloom. An increase in floral abundance can dilute parasite transmission between bees. Abstract: Parasites influence wild bee population dynamics and are regarded as one of the main drivers of wild bee decline. Most of these parasites are mainly transmitted between bee species via the use of shared floral resources. Disturbance of the plant-pollinator network at a location can hence disturb the transmission of these parasites. Expansion and intensification of agriculture, another major driver of wild bee decline, often disturbs local plant-pollinator networks by altering the availability and diversity of floral resources. Mass-flowering crops are an extreme example as they provide an abundance of floral resources for a short period of time, substantially altering the present plant-pollinator network. This likely has repercussions on parasite transmission in the pollinator community. Using the bloom of mass-flowering crops we tested the hypothesis that an increase in floral resources can dilute parasite transmission in the pollinator community. To test this, we analysed the presence of parasites in the pollen of the brood cell provisions of Osmia spp., collected from trap nests placed in apple and sweet cherry orchards. We collected pollen at several time intervals during and after mass bloom, and found that pollen collected during mass bloom had significantly lower parasite prevalence compared with pollen collected after mass bloom. Furthermore, using pollen barcoding data we found that the presence of MFCs in pollen was a good predictor for lower parasite prevalence. Taken together, our results indicate that an increase in flower availability can reduce parasite transmission between bees.